ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII SMP NEGERI PEKANBARU PADA MATERI GETARAN, GELOMBANG DAN BUNYI - Lia Amalia Azzahra; Mitri Irianti; Muhammad Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aimed to determine the level of critical thinking ability of students in grade VIII SMP Negeri Pekanbaru on vibrations, waves and sound materials. The population in this study is the students of class VIII SMP Negeri Pekanbaru that has implemented the Curriculum 2013 for four years be successive totaling 950 people. The sample was taken proportional random sampling so that the sample was 255 people. The research instrument is a matter of critical thinking skill test based on the indicator of critical thinking ability. Data were collected by providing tests to samples who had studied vibration, wave and sound materials. Data analysis in this research used descriptive analysis with percentage technique, which gives an idea about the level of critical thinking ability. The results of this study provide information that the average percentage of critical thinking ability of students in grade VIII SMP Negeri Pekanbaru is 69.88% with the level of critical thinking ability in the medium category.Keywords: Critical Thinking Ability, vibrations, waves and sound materials.